Enfermedad holandesa efectos y posibles soluciones (2013)
The revenue provided by mining allowed this sector to become one of the engines of national government. But these resources that were once viewed as an important input for the development of the nation, became one of the major concerns of the agricultural, industrial, livestock and even the same state, due to any negative effects generated by these resources.